Russian entrepreneurship in the formation of charitable activities: Yesterday, today, tomorrow - N. A. Shatalova (Вестник университета, 2024)
The article studies issues of Russian entrepreneurs’ philanthropic activities in retrospect. The author touches upon the historical contribution of entrepreneurs both as economic entities and as a social passionary force in Russian culture, education, and social protection development. Modern Russian entrepreneurs have different prerequisites for charitable activities based on the influence of corporate culture and corporate values. The social structure and the content of economic relations in Russia have been in the dynamics of change, but such a phenomenon as charity has not lost its significance. Charity acts as a form of entrepreneurs’ social responsibility to society. Charity in the pre-revolutionary period and at the present stage was influenced by various factors and historical circumstances. The study of this subject area involves the use of historiographical method and the study of biographies of prominent philanthropists. This allows us to understand more accurately the cause-and-effect relationships that condition the emergence and development of philanthropic practices. The results of the study show the lack of continuity between patrons of art in pre-revolutionary Russia and modern entrepreneurs, which is due to the difference in socio-cultural context. Analyzing the experience of charity is important for understanding the role of entrepreneurs in charitable activities functioning.